An Overview of the Rising Challenges in Implementing Industry 4.0 - Tay Shu Ing; T.C. Lee; S.W. Chan; J. Alipal; N. Abdul Hamid (International Journal of Supply Chain Management, 2019)
Industry 4.0 is the fourth industrial revolution that was first introduced in Germany which then becomes a trend of future manufacturing industries. The Industry 4.0 also referred as the umbrella concept for new industrial paradigm which consists of a number of future industry characteristics, were related to cyber-physical systems (CPS), internet of things (IoT), internet of services (IoS), robotics, big data, cloud manufacturing and augmented reality. By adopting these technologies as the key development in more intelligent manufacturing processes including devices, machines, modules, and products, the process of information exchange, action and control will stimulate each other, subsequently to an intelligent manufacturing environment. However, in order to fully utilize the advantages of industry 4.0, there are some challenges that need to be overcome. This paper reviews the challenges in implementing Industry 4.0. The literatures found in this paper mainly from Google Scholar, Science Direct and Emerald. In short, the challenges can be imparted into seven major categories. There are data management and Integration, knowledge-driven, process, security, capital, workforce, and education.